(untitled) (ADMPG Journal, 2025)
In view of the increase in financial concerns, especially among university students, about the changes caused by the 2020 crisis and considering the decrease in income, it is necessary to investigate how these individuals manage and control their finances. Thus, the present study aimed to compare the management of personal finances of students at the Federal University of Santa Catarina before and after the beginning of the Covid-19 pandemic. The survey was conducted with 171 undergraduate students from different courses, through an online questionnaire consisting of 23 questions. Most respondents were female and between 21 and 30 years old. The results showed that the respondents have very good financial attitudes and most of them thought they had a reasonable knowledge about personal finances. During the pandemic period, there was a substantial increase, over 10%, in financial management practice among university students. However, despite the fact that many carry out financial control, they still lack the knowledge and persistence to continue to properly plan their expenses and income. In addition, it`s important for respondents to review their financial control methods to verify their real efficiency. It is recommended to expand the study geographically and include more financial management descriptors to enrich the analyses.